Applied of Phase Equilibrium to Simulate Pressure Swing Distillation of 1-Butanol + Water Mixtures - Tetrisyanda, Rizky (Journal of Fundamentals and Applications of Chemical Engineering, 2023)
Butanol as fuel mixtures has been sufficiently proven to be able to reduce NOx and PM gas emissions. Water is a by-product produced in the butanol production process. The mixture of butanol and water system contains an azeotrope which cannot be separated using conventional distillation. Azeotropic distillation techniques have been developed quite a lot, one of which is Pressure Swing Distillation (PSD). In this study, the computational simulation were performed using commercial software Aspen Plus and thermodynamic model UNIQUAC. The configuration of operating conditions and equipment in the PSD for the 1-butanol and water system has effects on the need for supporting equipment and its techno-economic analysis. From the results of this simulation study, it is obtained that the PSD configuration with a High Pressure (HP) to Low Pressure (LP) design can obtain a 1-butanol product with a purity of 99.98% with a TAC (Total Annual Cost) of 0.64 (10g USD/year) and the cost of separating 1-butanol is 0.085 USD/kg and the cost for energy is 0.03 USD/kg.